2002
DOI: 10.1210/endo.143.4.8741
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor/IGF-Binding Protein-Related Protein-2 Is a Mediator in the Induction of Fibronectin by Advanced Glycosylation End-Products in Human Dermal Fibroblasts

Abstract: Expansion of extracellular matrix with fibrosis occurs in many tissues, including skin, as part of the end-organ complications in diabetes. Advanced glycosylation end-products (AGEs) have been implicated as a pathogenic factor in diabetic tissue fibrosis. Connective tissue growth factor (CTGF), also known as IGF-binding protein-related protein-2, induces extracellular matrix. We have recently shown that CTGF mRNA and protein are up-regulated by AGE treatment of cultured human dermal fibroblasts. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 43 publications
5
23
0
1
Order By: Relevance
“…18 19 AGEs induce fibronectin, a component of the retinal BM, 38 in dermal fibroblasts via upregulation of CTGF. 39 Thus, CTGF may well be involved in BM thickening in preclinical DR, and this notion is supported by our finding that CTGF is overexpressed in pericytes in the human diabetic retina, irrespective of changes related to clinical DR like vascular leakage.…”
Section: Discussionsupporting
confidence: 72%
“…18 19 AGEs induce fibronectin, a component of the retinal BM, 38 in dermal fibroblasts via upregulation of CTGF. 39 Thus, CTGF may well be involved in BM thickening in preclinical DR, and this notion is supported by our finding that CTGF is overexpressed in pericytes in the human diabetic retina, irrespective of changes related to clinical DR like vascular leakage.…”
Section: Discussionsupporting
confidence: 72%
“…Previous literature reported that chronic wounds in diabetes mainly occur due to the lack of different macromolecular proteins of the ECM (Maione et al, ; Pankov & Yamada, ). FN, as one composition of ECM, has been proved to be induced by CTGF through PKC signalling pathway in human dermal fibroblasts (Twigg et al, ).Therefore, we determined whether CTGF loaded on ADM scaffolds increases the expression of FN for accelerated diabetic wound healing through the PKC signalling pathway in this experiment. For comparison, CTGF + PKC inhibitor was loaded on ADM scaffolds to treat dorsal skin wounds in STZ‐induced diabetic mice with ADM as a control.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that an imbalance between gene expression of interstitial collagenases and gene expression of TIMP-1 contributed to extracellular matrix accumulation (26). Connective tissue growth factor (CTGF), a potent stimulator of collagen synthesis (27), consists of 349 amino acids with four distinct domains and induced by mechanical shear stress in vitro (28,29). As mentioned above, the balance of MMP and TIMP-1 is involved in the regulation of collagen degradation and CTGF contributed to collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%